Repurposing a photosynthetic antenna protein as a super-resolution microscopy label. Issue 1 (December 2017) - Barnett, Samuel; Hitchcock, Andrew; Mandal, Amit; Vasilev, Cvetelin; Yuen, Jonathan; Morby, James; Brindley, Amanda; Niedzwiedzki, Dariusz; Bryant, Donald; Cadby, Ashley; Holten, Dewey; Hunter, C.
Abstract Techniques such as Stochastic Optical Reconstruction Microscopy (STORM) and Structured Illumination Microscopy (SIM) have increased the achievable resolution of optical imaging, but few fluorescent proteins are suitable for super-resolution microscopy, particularly in the far-red and near-infrared emission range. Here we demonstrate the applicability of CpcA, a subunit of the photosynthetic antenna complex in cyanobacteria, for STORM and SIM imaging. The periodicity and width of fabricated nanoarrays of CpcA, with a covalently attached phycoerythrobilin (PEB) or phycocyanobilin (PCB) chromophore, matched the lines in reconstructed STORM images. SIM and STORM reconstructions ofEscherichia coli cells harbouring CpcA-labelled cytochromebd 1 ubiquinol oxidase in the cytoplasmic membrane show that CpcA-PEB and CpcA-PCB are suitable for super-resolution imagingin vivo . The stability, ease of production, small size and brightness of CpcA-PEB and CpcA-PCB demonstrate the potential of this largely unexplored protein family as novel probes for super-resolution microscopy.